Coal-fired power plant flue gas desulfurization wastewater treatment using constructed wetlands - Paredez, Jose Miguel (Kansas State University, 2014)
In the United States approximately 37% of the 4 trillion kWh of electricity is generated annually by combusting coal (USEPA, 2013). The abundance of coal, ease of storage, and transportation makes it affordable at a global scale (Ghose, 2009). However, the flue gas produced by combusting coal affects human health and the environment (USEPA, 2013). To comply with federal regulations coal-fired power plants have been implementing sulfur dioxide scrubbing systems such as flue gas desulfurization (FGD) systems (Alvarez-Ayuso et al., 2006). Although FGD systems have proven to reduce atmospheric emissions they create wastewater containing harmful pollutants. Constructed wetlands are increasingly being employed for the removal of these toxic trace elements from FGD wastewater. In this study the effectiveness of using a constructed wetland treatment system was explored as a possible remediation technology to treat FGD wastewater from a coal-fired power plant in Kansas. To simulate constructed wetlands, a continuous flow-through column experiment was conducted with undiluted FGD wastewater and surface sediment from a power plant in Kansas. To optimize the performance of a CWTS the following hypotheses were tested: 1) decreasing the flow rate improves the performance of the treatment wetlands due to an increase in reaction time, 2) the introduction of microbial cultures (inoculum) will increase the retention capacity of the columns since constructed wetlands improve water quality through biological process, 3) the introduction of a labile carbon source will improve the retention capacity of the columns since microorganisms require an electron donor to perform life functions such as cell maintenance and synthesis. Although the FGD wastewater collected possessed a negligible concentration of arsenic, the mobilization of arsenic has been observed in reducing sediments of wetland environments. Therefore, constructed wetlands may also represent an environment where the mobilization of arsenic is possible. This led us to test the following hypothesis: 4) Reducing environments will cause arsenic desorption and dissolution causing the mobilization of arsenic. As far as removal of the constituents of concern (arsenic, selenium, nitrate, and sulfate) in the column experiments, only sulfate removal increased as a result of decreasing the flow rate by half (1/2Q). In addition, sulfate-S exhibited greater removal as a result of adding organic carbon to the FGD solution when compared to the control (at 1/2Q). Moderate selenium removal was observed; over 60% of selenium in the influent was found to accumulate in the soil. By contrast, arsenic concentrations increased in the effluent of the 1/2Q columns, most likely by dissolution and release of sorbed arsenic. When compared to the control (at 1/2Q), arsenic dissolution decreased as a result of adding inoculum to the columns. Dissolved arsenic concentrations in the effluent of columns with FGD solution amended with organic carbon reached 168 mg/L. These results suggest that native Kansas soils placed in a constructed wetland configuration and amended with labile carbon do possess an environment where the mobilization of arsenic is possible.
Keywords: Wastewater; Constructed Wetlands; Arsenic; Selenium; Power Plants; Flue Gas Desulfurization; Civil Engineering (0543)